Using process features to investigate scientific problem-solving in large-scale assessments - Gong, Tao; Shuai, Lan; Jiang, Yang; Arslan, Burcu (Frontiers in Psychology, 2023)
This study investigates the process data from scientific inquiry tasks of fair tests (requiring test-takers to manipulate a target variable while keeping other(s) constant) and exhaustive tests (requiring test-takers to construct all combinations of given variables) in the National Assessment of Educational Progress program. We identify significant associations between item scores and temporal features of preparation time, execution time, and mean execution time. Reflecting respectively durations of action planning and execution, and execution efficiency, these process features quantitatively differentiate the high- and low-performing students: in the fair tests, high-performing students tended to exhibit shorter execution time than low-performing ones, but in the exhaustive tests, they showed longer execution time; and in both types of tests, high-performing students had shorter mean execution time than low-performing ones. This study enriches process features reflecting scientific problem-solving process and competence and sheds important light on how to improve performance in large-scale, online delivered scientific inquiry tasks.